Corporate income tax reforms and international tax competition - Devereux, M; Griffith, R; Klemm, A (2002)
This paper analyses the development of taxes on corporate income in EU and G7 countries over the last two decades. We establish a number of stylized facts about their development. Tax-cutting and base-broadening reforms have had the effect that, on average across EU and G7 countries, effective tax rates on marginal investment have remained fairly stable, but those on more profitable investments have fallen. We discuss two possible explanations of these stylized facts arising from alternative forms of tax competition. First, governments may be responding to a fall in the cost of income shifting, which puts downward pressure on the statutory tax rate. Second, reforms are consistent with competition for more profitable projects, in particular those earned by multinational firms.